RAISING LEARNER AWARENESS OF LOCAL WISDOM IN TOUR-RELATED PROJECT TEACHING - Sa-ngiamwibool, Amporn (Indonesian Journal of Applied Linguistics, 2012)
Abstract: This study investigated how CLT (Communicative Language Teaching) and awareness-raising enhanced Thai learners’ awareness of their local wisdom in a tour-related project work with three specific purposes, which were to explore how the learners interacted with textual representations of their local wisdom to create their project, what extent CLT and awareness-raising tasks developed their communicative competence of the target language, and what object of awareness that the tasks could help the learners realize while working on their projects. This study was triangulated. The elicitation instruments were project instructions, CLT and awareness-raising tasks, pretests and posttests based on TOEIC (Test of English for International Communication), learner logs, interviews, and observation notes. The study revealed that, first, on the awareness of local wisdom in a tour-related project work, the learners interacted with textual representations of their local wisdom through theme-centered learning process. Second, on the enhancement of CLT and awareness-raising, CLT allowed the learners to deal with interactive, spontaneous, and more meaningful communication actively while awareness-raising helped the learners consciously focus on semantic, linguistic, and pragmatic aspects of the target language. Lastly, on object of awareness, CLT and awareness-raising tasks could lead the learners to realize these objects of awareness: nature of experiential learning, subject content, and skill content. For pedagogical implications, project-based teaching with the support of CLT and awareness-raising tasks can raise learner awareness of local wisdom in tour-related topics effectively. Pedagogical implications illustrated some practical applications of CLT and awareness-raising tasks for enhancing learner awareness in ESP project work in a Thai classroom. Future inquiry should replicate this study or apply to business or other ESP project instructions. Keywords: tour-related project work of local wisdom, communicative language teaching (CLT) or communicative language learning (CLL), awareness-raising or consciousness-raising (C-R)